Puerarin Relieves Paclitaxel-Induced Neuropathic Pain: The Role of Nav1.8 β1 Subunit of Sensory Neurons - Zhang, Xiao-Long; Cao, Xian-Ying; Lai, Ren-Chun; Xie, Man-Xiu; Zeng, Wei-An (Frontiers in Pharmacology, 2019)
Currently there is no effective treatment available for clinical patients suffering from neuropathic pain induced by chemotherapy paclitaxel. Puerarin is a major isoflavonoid extracted from the Chinese medical herb kudzu root, which has been used for treatment of cardiovascular disorders and brain injury. Here, we found that puerarin dose-dependently alleviated paclitaxel-induced neuropathic pain. At the same time, puerarin preferentially reduced the excitability and blocked the voltage-gated sodium (Nav) channels of dorsal root ganglion (DRG) neurons from paclitaxel-induced neuropathic pain rats. Furthermore, puerarin was a more potent blocker of tetrodotoxin-resistant (TTX-R) Nav channels than of tetrodotoxin-sensitive (TTX-S) Nav channels in chronic pain rats’ DRG neurons. In addition, puerarin had a stronger blocking effect on Nav1.8 channels in DRG neurons of neuropathic pain rats and β1 subunit siRNA can abolish this selective blocking effect on Nav1.8. Together, these results suggested that puerarin may preferentially block β1 subunit of Nav1.8 in sensory neurons contributed to its anti-paclitaxel induced neuropathic pain effect.